Eksploitasi Awak Kapal Asing: Tanggung Jawab Negara Bendera terhadap ABK Indonesia di Kapal China Long Xing 629 - Dharmawan, Yudi; Sipahutar, Bernard; Farisi, Mochammad (Uti Possidetis: Journal of International Law, 2022)
This article discusses the form of legal protection and the flag state's responsibility for Indonesian crew members who work on foreign ships against exploitation in terms of international law. This article uses a normative juridical method, which is a method carried out by researching library materials or secondary data. The results of this articel discovered,  that state flag responsibility for the legal protections for ship crews has to be done in a few ways such as conducting an investigation of the Long Xing 629 or the ship’s company.  If it proven that there had been a violation of human rights, the state flag have to prosecute the perpetrators of the crime that had committed on that ship. This responsibility have to done, cause the legal statue’s of protection for the ships crew who worked on foreign vessels has been regulated under general nor specific international law instruments, as well others forms of legal protection are also given by international organizations such as ILO that specifically handles unternational labor issues.